Malignant Melanoma with Probable Smooth Muscle Differentiation - Aya Morimoto; Jun Asai; Yusuke Wakabayashi; Satoshi Komori; Keiji Hanada; Hideya Takenaka; Eiichi Konishi; Norito Katoh (Karger Publishers, 2014)
Malignant melanomas occasionally exhibit various divergent differentiation types. Of these, smooth muscle differentiation is extremely rare; only 1 case has been reported in the literature until recently. We report an extremely rare case of malignant melanoma with smooth muscle differentiation, which appeared as an amelanotic reddish nodule on the left toe.